PENGARUH MEKANISME DAN AKTIVITAS TATA KELOLA PERUSAHAAN YANG BAIK, KARAKTERISTIK PERUSAHAAN, DAN KARAKTERISTIK AUDITOR TERHADAP AUDIT REPORT LAG - Fidanza, Muhammad Giliyen; Ghozali, Imam (Diponegoro Journal of Accounting, 2024)
The purpose of this study is to examine the influence of good corporate governance mechanisms and activities, company characteristics, and auditor characteristics on audit report lag. The independent variables used in this study are board size, board independence, audit committee size, audit committee meeting frequency, firm size, profitability, and auditor reputation. The dependent variable in this study is audit report lag.The population used in this study is manufacturing sector companies listed on the Indonesia Stock Exchange. Using the purposive sampling method, 417 samples were selected, which are manufacturing sector companies that published annual reports during the period 2020-2022. Multiple regression analysis is employed in this study to examine the effects of board size, board independence, audit committee size, audit committee meeting frequency, firm size, profitability, and auditor reputation on audit report lag.The results of this study indicate that board size and auditor reputation have a significant negative influence on audit report lag.